2005
DOI: 10.1128/jcm.43.4.1612-1616.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Ofloxacin Resistance in Mycobacterium tuberculosis by Two Low-Cost Colorimetric Methods: Resazurin and Nitrate Reductase Assays

Abstract: We have evaluated the performance of two rapid, low-cost methods for the detection of ofloxacin (OFX) resistance with 95 Mycobacterium tuberculosis isolates from countries with high multidrug-resistant tuberculosis endemicity. Results obtained by nitrate reductase and resazurin assays showed 100% agreement with those of the proportion method on 7H11 agar using 2 g of OFX/ml. We confirmed the resistance of all isolates found to be resistant to OFX by the Mycobacterium Growth Indicator Tube system, and complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…The critical concentration for OFX was the same as that recommended by the other two studies (13,18) using the manual MGIT but also by Rüsch-Gerdes et al (24) using the automated MGIT 960 system. On the contrary, in the study of Krüüner et al (12), the authors recommend the use of a critical concentration of 1 g/ml of OFX for the MGIT 960.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The critical concentration for OFX was the same as that recommended by the other two studies (13,18) using the manual MGIT but also by Rüsch-Gerdes et al (24) using the automated MGIT 960 system. On the contrary, in the study of Krüüner et al (12), the authors recommend the use of a critical concentration of 1 g/ml of OFX for the MGIT 960.…”
Section: Discussionsupporting
confidence: 49%
“…Two multicenter studies using the BACTEC MGIT 960 automated system for validation of DST of M. tuberculosis to second-line drugs have been described in the literature. Also, only three studies have been reported in the literature using the manual MGIT for second-line drugs, and they focused on only two drugs (3,13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Resistant strains will reduce the nitrate revealed by a pink-red colour in the medium, while susceptible strains will loose this capacity as they are inhibited by the antibiotic, leaving the medium colourless [79]. The test has been recently evaluated for DST to first-and second-line drugs with good results [80,81]. It has the added advantage of using the same format and culture medium as used in the standard proportion method.…”
Section: Phenotypic Methodsmentioning
confidence: 99%
“…Recently, alternative rapid methods have been developed (13). Among them, the nitrate reductase assay (NRA) on Löwenstein-Jensen (LJ) medium is simple to perform and has been successfully implemented in low-income countries (7,13,14). This test is based on the ability of Mycobacterium tuberculosis to reduce nitrate to nitrite, which is revealed as a color change in the culture medium, using the Griess method (10).…”
mentioning
confidence: 99%